2021
DOI: 10.31004/basicedu.v5i4.993
|View full text |Cite
|
Sign up to set email alerts
|

Kemunculan Aspek Karakter Siswa SD melalui Pembelajaran RADEC dengan Menggunakan WhatsApp pada Materi Siklus Air

Abstract: Penelitian ini bertujuan untuk melihat kemunculan aspek karakter siswa pada setiap tahapan model pembelajaran RADEC. Aktivitas pembelajaran pada penelitian ini dilaksanakan secara daring melalui aplikasi WhatsApp. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Partisipan penelitian terdiri atas 35 orang siswa kelas V di salah satu sekolah dasar negeri di Kecamatan Sumedang Selatan, Kabupaten Sumedang. Subjek ditentukan secara purposeful sampling. Pengumpulan data dilakukan melalui wawancar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
2
2
1
8
Order By: Relevance
“…However, this form of collaboration has yet to work as expected, namely helping each other when having difficulties, appreciating the work of their group member, and exchanging ideas and opinions. This is different with previous research which found that at the discuss stage, students discuss to reach an agreement with all group members (Sukmawati et al, 2021). However, the findings of this research are similar with the research by Hartina et al (2022) that group discussions have not divided tasks well.…”
Section: Create Collaborationcontrasting
confidence: 99%
See 2 more Smart Citations
“…However, this form of collaboration has yet to work as expected, namely helping each other when having difficulties, appreciating the work of their group member, and exchanging ideas and opinions. This is different with previous research which found that at the discuss stage, students discuss to reach an agreement with all group members (Sukmawati et al, 2021). However, the findings of this research are similar with the research by Hartina et al (2022) that group discussions have not divided tasks well.…”
Section: Create Collaborationcontrasting
confidence: 99%
“…It can be seen that each group members contribute to complete the assignment. This research has similarities with previous research that student shows their desire to contribute in creating projects through a deliberation process (Sukmawati et al, 2021). There are group that need more complete tools and material, so other groups helped by giving the tools to the group that needs the tools.…”
Section: Create Collaborationsupporting
confidence: 69%
See 1 more Smart Citation
“…Pada tahap Discuss dan Explain karakter yang muncul yaitu sikap religious, nasionalis, mandiri, gotongroyong, dan integritas, sedangkan pada tahap Create karakter yang muncul yaitu sikap religious, nasionalis, mandiri serta gotong royong. Karakter yang muncul ini ditinjau saat pelaksanaan pembelajaran berlangsung (Sukmawati, Sopandi, Sujana, & Muharam, 2021).…”
Section: Model Pembelajaran Radec Secara Daringunclassified
“…Melalui pertanyaan prapembelajaran siswa dilatih untuk menjawaban sendiri pertanyaan-pertanyaan yang diberikan. Sukmawati et al (2021) menyatakan bahwa melalui model RADEC khususnya dalam pemberian pertanyaan prapembelajaran salah satunya dapat menumbuhkan karakter kemandirian dalam belajar. Teori konstruktivisme yang dijelaskan oleh Vygotsky (dalam Smagorinsky, 2018) menyatakan bahwa pada zona of proximal development peran dari guru adalah sebagai mediator untuk mendorong dan menjembatani siswa dalam upaya membangun pengetahuannya.…”
Section: Hasil Dan Pembahasanunclassified